Micro-political game playing in Lidl: A comparison of store-level employment relations. (September 2015) - Geppert, Mike; Williams, Karen; Wortmann, Michael
This article examines how the rules of micro-political game playing, based on the global standardization and cost leadership approach of a European 'hard discounter', are interpreted in practice in Finland, Germany, Ireland, Spain and the UK. We find that small store size, together with centralized authority relations and power structures, make it difficult for actors to engage effectively in coalition-building and political strategies to influence work and employment. Our comparison also reveals that the interpretation of employment-related rules of the game is country-specific. In Finland, and to some extent in Spain, national employment systems enabled employees to build more robust toolkits for playing micro-political games than in the other countries investigated.